Working with Legacy Systems : a Practical Guide to Looking after and Maintaining the Systems We Inherit. - Annett, Robert (Packt Publishing, Limited, 2019)
The IT industry is obsessed with new technologies. Courses, books, and magazines mostly focus on what is new. Starting with what a legacy system looks like to applying various techniques for maintaining and securing these systems, this book gives you all the knowledge you need to maintain a legacy system.